Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How do you solve $y''+\frac{x}{2}y'+y=0$ where $y'=\frac{\partial y}{\partial x}$

What is confusing me is that once I say $g=y'$ I'm left with :

$g'+\frac{x}{2}g+y=0$

I can't use seperation by parts here. How would one proceed here? Thank you.

Best

share|improve this question
    
Use power series technique. –  Mhenni Benghorbal Oct 28 '13 at 20:12
1  
There are two unknown functions in your DE: $g'+\frac{x}{2}g+y=0$. To solve this for $g$ you have to know what $y$ is first. When you put $y$ in terms of $g$ you see that there is also an integral of $g$ there. –  user40615 Oct 29 '13 at 11:55

1 Answer 1

In fact this question is similar to solution of ordinary differential equations:

Let $y=\int_Ce^{xu}K(u)~du$ ,

Then $(\int_Ce^{xu}K(u)~du)''+\dfrac{x}{2}(\int_Ce^{xu}K(u)~du)'+\int_Ce^{xu}K(u)~du=0$

$\int_Cu^2e^{xu}K(u)~du+\dfrac{x}{2}\int_Cue^{xu}K(u)~du+\int_Ce^{xu}K(u)~du=0$

$\int_C(u^2+1)e^{xu}K(u)~du+\int_C\dfrac{ue^{xu}K(u)}{2}d(xu)=0$

$\int_C(u^2+1)e^{xu}K(u)~du+\int_C\dfrac{uK(u)}{2}d(e^{xu})=0$

$\int_C(u^2+1)e^{xu}K(u)~du+\left[\dfrac{ue^{xu}K(u)}{2}\right]_C-\int_Ce^{xu}~d\left(\dfrac{uK(u)}{2}\right)=0$

$\int_C(u^2+1)e^{xu}K(u)~du+\left[\dfrac{ue^{xu}K(u)}{2}\right]_C-\int_Ce^{xu}\dfrac{uK'(u)+K(u)}{2}du=0$

$\int_C(u^2+1)e^{xu}K(u)~du+\left[\dfrac{ue^{xu}K(u)}{2}\right]_C-\int_Ce^{xu}\dfrac{uK'(u)-(2u^2+1)K(u)}{2}du=0$

$\therefore uK'(u)-(2u^2+1)K(u)=0$

$uK'(u)=(2u^2+1)K(u)$

$\dfrac{K'(u)}{K(u)}=2u+\dfrac{1}{u}$

$\int\dfrac{K'(u)}{K(u)}du=\int\left(2u+\dfrac{1}{u}\right)du$

$\ln K(u)=u^2+\ln u+c_1$

$K(u)=cue^{u^2}$

$\therefore y=\int_Ccue^{u^2+xu}~du$

But since the above procedure in fact suitable for any complex number $u$ ,

$\therefore y_n=\int_{a_n}^{b_n}c_n(k_nt)e^{(k_nt)^2+xk_nt}~d(k_nt)={k_n}^2c_n\int_{a_n}^{b_n}te^{{k_n}^2t^2+k_nxt}~dt$

For some $x$-independent real number choices of $a_n$ and $b_n$ and $x$-independent complex number choices of $k_n$ such that:

$\lim\limits_{t\to a_n}t^2e^{{k_n}^2t^2+k_nxt}=\lim\limits_{t\to b_n}t^2e^{{k_n}^2t^2+k_nxt}$

$\int_{a_n}^{b_n}te^{{k_n}^2t^2+k_nxt}~dt$ converges

For $n=1$, the best choice is $a_1=0$ , $b_1=\infty$ , $k_1=\pm i$

$\therefore y=C_1\int_0^\infty te^{-t^2}\cos xt~dt$ or $C_1\int_0^\infty te^{-t^2}\sin xt~dt$

Hence $y=C_1\int_0^\infty te^{-t^2}\sin xt~dt+C_2\int_0^\infty te^{-t^2}\cos xt~dt$

share|improve this answer
    
Well done! This was not a trivial problem –  nbubis Nov 1 '13 at 5:35

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.